2020
DOI: 10.1097/mnh.0000000000000574
|View full text |Cite
|
Sign up to set email alerts
|

Plant-based diets for prevention and management of chronic kidney disease

Abstract: Purpose of reviewPlant-based diets have been used with growing popularity for the treatment of a wide range of lifestylerelated diseases, including diabetes, hypertension, and obesity. With the reinvigoration of the dietary management of chronic kidney disease (CKD) and the use of low protein diets for secondary prevention of CKD to delay or prevent dialysis therapy, there is an increasing interest in the potential role of plant-based diets for these patients. Recent findingsRecently, a body of evidence relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 32 publications
0
43
0
Order By: Relevance
“…A recent comprehensive and critical review of the literature concluded that daily red meat consumption over years may increase CKD risk, whereas fruit and vegetable proteins may be renal protective [18]. Prior studies summarized by some of the authors of this article [31,33,34,[55][56][57][58][59][60][61] suggest that animal-based protein is harmful to kidney health, while a plant-dominant diet may slow CKD progression. A landmark study was presented by Kontessis et al [62], who studied volunteers fed for 3 weeks with a vegetable-based diet (N = 10), an animal protein diet (N = 10), or an animal protein diet supplemented with fiber (N = 7), all with the same amount of total protein; animal-based protein diets increased GFR more than similar amounts of plant-based proteins, i.e., higher glomerular hyperfiltration was observed with more meat and less vegetable-derived proteins [62].…”
Section: Plant-based Foods Have a Favorable Impact On Kidney Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent comprehensive and critical review of the literature concluded that daily red meat consumption over years may increase CKD risk, whereas fruit and vegetable proteins may be renal protective [18]. Prior studies summarized by some of the authors of this article [31,33,34,[55][56][57][58][59][60][61] suggest that animal-based protein is harmful to kidney health, while a plant-dominant diet may slow CKD progression. A landmark study was presented by Kontessis et al [62], who studied volunteers fed for 3 weeks with a vegetable-based diet (N = 10), an animal protein diet (N = 10), or an animal protein diet supplemented with fiber (N = 7), all with the same amount of total protein; animal-based protein diets increased GFR more than similar amounts of plant-based proteins, i.e., higher glomerular hyperfiltration was observed with more meat and less vegetable-derived proteins [62].…”
Section: Plant-based Foods Have a Favorable Impact On Kidney Healthmentioning
confidence: 99%
“…However, it is prudent that in patients who may develop signs of PEW or acute kidney injury (AKI), higher DPI targets should be temporarily used until PEW or AKI is resolved. On the other hand, if there is concern related to the likelihood of obesity and hyperglycemia, patients and providers should be reassured that LPD therapy in CKD has not been shown to be associated with such risks, and indeed, an LPD with plant-based sources has salutary effects on insulin resistance and glycemic index, as long as total calorie intake remains within the targeted range of 30-35 kcal/kg/day [34,55].…”
Section: Safety and Adequacy Of A Plant-dominant Low-protein Dietmentioning
confidence: 99%
“…34 A recent comprehensive and critical review of the literature concluded that daily red meat consumption over years may increase CKD risk, whereas fruit and vegetable proteins may be renal protective. 18 Prior studies summarized by some of the authors of this article 29,31,32,[35][36][37] and others [38][39][40][41] suggest that animal-based protein is harmful to kidney health, while a plant-dominant diet may slow CKD progression. A landmark study was presented by Kontessis et al 42 who studied volunteers fed for 3 weeks with a vegetable-based diet (N=10), an animal protein diet (N=10), or an animal protein diet supplemented with fiber (N=7), all with the same amount of total protein; animal-based protein diets increased GFR more than similar amounts of plant-based proteins, i.e., higher glomerular hyperfiltration was observed with more meat and less vegetable-derived proteins.…”
Section: Plant-based Foods Have a Favorable Impact On Kidney Healthmentioning
confidence: 99%
“…On the other hand, if there is concern related to the likelihood of obesity and hyperglycemia, patients and providers should be reassured that LPD therapy in CKD has not been shown to be associated with such risks, and indeed a LPD with plant-based sources has salutary effects on insulin resistance and glycemic index, as long as total calorie intake remains within the targeted range of 30-35 kcal/kg/day. 32,35 Another frequently stated concern is the perceived risk of hyperkalemia. We are not aware of scientific evidence to support the cultural dogma that dietary potassium restriction in CKD improves outcomes.…”
Section: Safety and Adequacy Of A Plant-dominant Low-protein Dietmentioning
confidence: 99%
“…The consumption of protein is around 1.2 to 1.4 g/kg/day, mostly from animal sources, according to the National Health and Nutrition Examination Survey (NHANES) [8]. If a high-protein diet and the keto diet have been suggested to fight against obesity and diabetes, these diets have not been as effective as expected for glycemic control or weight loss in randomized controlled trials (RCT) [9,10]. This calls for a reconsideration of AAs functions in nutrition, now based upon health-related criteria to limit the negative effect on kidney health over time across populations with or at-risk for CKD.…”
Section: Introductionmentioning
confidence: 99%